Temperature-dependent egg production and egg hatching rates of small egg-carrying and broadcast-spawning copepods Oithona similis, Microsetella norvegica and Microcalanus pusillus - Barth-Jensen, Coralie; Koski, Marja; Varpe, Øystein; Glad, Peter; Wangensteen, Owen S.; Præbel, Kim; Svensen, Camilla (Journal of Plankton Research, 2020)
Reproductive rates of copepods are temperature-dependent, but poorly known for small copepods at low temperatures, hindering the predictions of population dynamics and secondary production in high-latitude ecosystems. We investigated egg hatching rates, hatching success and egg production of the small copepods Oithona similis and Microsetella norvegica (sac spawners) and Microcalanus pusillus (broadcast spawner) between March and August. Incubations were performed at ecologically relevant temperatures between 1.3 and 13.2°C, and egg production rates were calculated. All egg hatching rates were positively correlated to temperature, although with large species-specific differences. At the lowest temperatures, M. pusillus eggs hatched within 4 days, whereas the eggs from sac spawners took 3–8 weeks to hatch. The egg hatching success was ≤25% for M. pusillus , >75% for O. similis and variable for M. norvegica . The maximum weight-specific egg production rate (μg C μg −1 C d −1 ) of M. pusillus was higher (0.22) than O. similis (0.12) and M. norvegica (0.06). M. norvegica reproduction peaked at 6–8°C, the prevailing in situ temperatures during its reproductive period. The difference in reproductive rates indicates species-specific thermal plasticity for the three copepods, which could have implications for present and future population dynamics of the species in arctic fjords.